Field tests of a highly flexible downwind ultralight rotor to mimic a 13-MW turbine rotor. Issue 3 (1st May 2022) - Loth, Eric; Ananda, Gavin; Chetan, Mayank; Damiani, Rick; Todd Griffith, D.; Johnson, Kathryn; Kianbakht, Sepideh; Kaminski, Meghan; Pao, Lucy; Phadnis, Mandar; Qin, Chao (Chris); Scholbrock, Andy; et al.
Abstract: Offshore extreme-scale turbines of 20–25 MW in size may offer reduced energy costs. The technical barriers at these extreme scales include escalating blade masses with increased flexibility as well as high gravity loads and tower-strike issues. These barriers may be addressed with a load-aligning downwind turbine. To investigate this type of design, a field test campaign was conducted with an aeroelastically scaled rotor, termed the Segmented Ultralight Morphing Rotor Demonstrator (SUMR-D). The tests were conducted on the Controls Advanced Research Turbine at the National Renewable Energy Laboratory. The paper gives an overviewof the experimental diagnostics, blade design, and results of the field campaign, as well as makes conclusions and recommendations regarding extreme-scale highly flexible downwind rotors.